Ceropegia stylesii (Apocynaceae-Asclepiadoideae)—a novel species with rotate flowers from Ngome, South Africa - Heiduk, Annemarie (Phytotaxa, 2023)
A novel species of Ceropegia sect. Bowkerianae (Apocynaceae: Asclepiadoideae-Ceropegieae-Stapeliinae), C. stylesii, is described from Ngome in northern KwaZulu-Natal, South Africa. This new species is vegetatively similar to C. gerrardii. The rotate non-trapping flowers of C. stylesii superficially appear to be miniature versions of a dark-flowered form of C. gerrardii, with which it is sympatric. Ceropegia stylesii is exceptionally rare with fewer than 10 individuals observed at two localities; its habitat is under anthropogenic threat. Ceropegia stylesii is considered as Critically Endangered (CR) according to IUCN criteria.